The governance of offshoring and its effects at home: The role of codetermination in the international organization of German firms - Allessandro Bramucci; Antonello Zanfei (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
This paper focuses on the links between labor market institutions and offshoring, with specific reference to the role of codetermination in shaping the international operations of German firms. We use case studies to illustrate how works councils deal with three important aspects of offshoring processes: the timeliness of information they receive from the management, the negotiation of compensation mechanisms and the design of alternative strategies. While we found no evidence of works councils impeding offshoring, there are elements to suggest that they may influence the way such decisions are taken, and moderate their effects on employment in the home country.
Keywords: F21; J53; L22; 330; Offshoring; Labor market institutions; Codetermination